JEJAK PEMERINTAHAN DARURAT REPUBLIK INDONESIA(PDRI) DI JORONG BULIAN NAGARI BIDAR ALAM KABUPATEN SOLOK SELATAN (1948-1949) - Cici Arifin; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: During his second Dutch military aggression against the Republic of Indonesia on December 19,1948, he succeeded in seizing Yogyakarta and at the same time arresting President Soekarno and Vice President Mohammad Hatta. The President and Vice President had sent a wire (telegram) addressed to Mr. Syafruddin Prawiranegara, who was ordered to form an emergency government in Sumatra. The guerrilla trip of the Republic of Indonesia Emergency Government up to the South Solok district is the longest place to stay in JorongBulianNagariBidarAlam. During Mr.SyafruddinPrawiranegara and the PDRI cabinet lived and settled there, regardless of the role of the local communityThe purpose of this study is 1) To find out the chronology of the establishment of the Republic of Indonesia Emergency Government in JorongBulian, BidarAlamNagari, South Solok Regency, 2) To find out the participation of JorongBulian community, BidarAlamNagari, South Solok Regency against the Republic of Indonesia Emergency Government 1948-1949, 3) To find out the traces of the Republic of Indonesia's emergency government in JorongBulian, BidarAlamNagari, South Solok district in 1948-1949, 4) To find out the situation of BulianJorong, BidarAlamNagari, South Solok Regency after the Republic of Emergency Government Indonesia and the present. The method used is a qualitative method with a historical approach and data collection techniques in the form of interviews, observation and documentation. The results of this study are that the community is still shoulder to shoulder in maintaining PDRI's footsteps and cares about the history of PDRI's journey, as well as the community's hope for the government to help maintain and intensify the history of PDRI to the present generation.Key Words: Trace, PDRI, South Solok.